Development of multi-service code family for spectral amplitude coding - optical code division multiple access systems - Kaka, Majid Hayas (2013)
In recent years Optical Code Division Multiple Access (OCDMA) technique received research attention due to its advantages including high-speed asynchronous low-latency access networking, dynamic bandwidth assignment and secured transmission. Among several encoding techniques developed for OCDMA systems,Spectral Amplitude Coding (SAC) is known as a suitable option to provide the Quality of Service (QoS) in optical communication networks by varying the code length, weight or both. SAC also has other advantages such as simplicity and lower cost of system components. In this thesis, a family of novel spreading sequences is constructed, called a Multi-Service (MS) code have been proposed for SAC-OCDMA system, to suppress the MAI consequently mitigate the Phase Induced Intensity Noise (PIIN), accommodate large number of users and enhanced the optical network capacity as well as offering service differentiation in optical domain. This proposed code has its own advantage because it could generate code-words in flexible way by setting variable basic codes at fixed code weight. The performance of the proposed code is demonstrated via mathematical simulation and it is shown that with 3.75 THz line width Broadband Source, MS code supports up to 10 users simultaneously at satisfactory Bit Error Rate (BER) of 10-9, choosing code weight of 4 and optimizing number of users per sequence when the bit-rate is 622 Mbps. Furthermore, the results showed that in higher bit-rate e.g. 5 and 10 Gbps, MS with code weight of 4 supports up to 15 and 7 active users respectively. Thus,from the results it indicates that MS code does not only preserve the capability of suppressing MAI, but also improves BER performance due to low cross-correlation (Ac) between code sequences.(I.E,O <Ac<1). Moreover, in the simulation analyses the software, OptiSystemTM version 10 was utilized to simulate the MS code system. The effects of various parameters such as fiber distance, bit rate, received optical power on the SAC-OCDMA system havebeen studied and compared, using the MS, Modified Quadratic Congruence (MQC), Khazani Syed (KS) and Random Diagonal (RD) codes. Based on the simulation results, performance of MS code outperformed former codes when the number of basic codes, NB was optimally chosen. Finally, the MS code was applied to one of the OCDMA applications which is Triple-Play services (audio, data, and video) with different QoS requirements. The proposed system used the dynamic basic codes (NB) feature of MS code to provide different QoS metrics for different users with fixed code weight. It is shown that optimum performance of specific NB can be obtained with a proper choice of supportable users. Codes that used lower value of NB always have smaller error probability. Hence, overall network performance can be improved if the number of lower NB users is larger in the multimedia applications. Due to the major advantages of the MS code, with a fewer number of weights, the cost and the complexity of the system is reduced comparing with other QoS codes. Hereby, MS code seems to be a good candidate for providing QoS applications.